Character and environmental lability of cyanobacteria‐derived dissolved organic matter. Issue 2 (9th October 2020) - Patriarca, Claudia; Sedano‐Núñez, Vicente T.; Garcia, Sarahi L.; Bergquist, Jonas; Bertilsson, Stefan; Sjöberg, Per J. R.; Tranvik, Lars J.; Hawkes, Jeffrey A.
Abstract: Autotrophic dissolved organic matter (DOM) is central to the carbon biogeochemistry of aquatic systems, and the full complexity of autotrophic DOM has not been extensively studied, particularly by high‐resolution mass spectrometry (HRMS). Terrestrial DOM tends to dominate HRMS studies in freshwaters due to the propensity of such compounds to ionize by negative mode electrospray, and possibly also because ionizable DOM produced by autotrophy is decreased to low steady‐state concentrations by heterotrophic bacteria. In this study, we investigated the character of DOM produced by the widespread cyanobacteria Microcystis aeruginosa using high‐pressure liquid chromatography—electrospray ionization—high‐resolution mass spectrometry. M. aeruginosa produced thousands of detectable compounds in axenic culture. These compounds were chromatographically resolved and the majority were assigned to aliphatic formulas with a broad polarity range. We found that the DOM produced by M. aeruginosa was highly susceptible to removal by heterotrophic freshwater bacteria, supporting the hypothesis that this autotroph‐derived organic material is highly labile and accordingly only seen at low concentrations in natural settings.